Factors associated with success in the oral part of the European Diploma in Intensive Care. (November 2017) - Waldauf, Petr; Rubulotta, Francesca; Sitzwohl, Christian; Elbers, Paul; Girbes, Armand; Saha, Rajnish; Marsh, Brian; Kumar, Ravindra; Maggiorini, Marco; Duška, František
Introduction: The oral part of European Diploma in Intensive Care diploma examinations changed in 2013 into an objective structured clinical examination-type exam. This step was undertaken to provide a fair and reproducible clinical exam. All candidates face identical questions with predefined correct answers simultaneously in seven high throughput exam centres on the same day. We describe the factors that are associated with success in part 2 European Diploma in Intensive Care exam. Methods: We prospectively collected self-reported data from all candidates sitting European Diploma in Intensive Care part 2 in 2015, namely demographics, professional background and attendance to a European Diploma in Intensive Care part 2 or generic objective structured clinical examination preparatory courses. After testing association with success (with cutoff at p < 0.10) and co-linearity of these factors as independent variables, we performed a multivariate logistical analysis, with binary exam outcome (pass/fail) as the dependent variable. Structural equation modelling was used to gain further insight into relations among determinants of success in the oral part of the European Diploma in Intensive Care. Results: Out of 427 candidates sitting the exam, completed data from 341 (80%) were available for analysis. The following candidates' factors were associated with increased chance of success: English as native language (odds ratio 4.3 (95% CI 1.7–10.7)), use of Patient-centred Acute Care Training e-learning programme module (odds ratios 2.0 (1.2–3.3)), working in an EU country (odds ratios 2.5 (1.5–4.3)), and better results in the written part of the European Diploma in Intensive Care (for each additional SD of 6.1 points odds ratios 1.9 (1.4–2.4)). Chance of success in the European Diploma in Intensive Care 2 decreased with increased candidates 'age (for each additional SD of 5.5 years odds ratios 0.67 (0.51–0.87)). Exam centres (7 in total) could be clustered into 3 groups with similar success rates. There were significant differences in exam outcomes among these 3 groups of exam centres even after adjustment to known candidates' factors (G1 vs G2 odds ratios 2.4 (1.4–4.1); G1 vs G3 odds ratios 9.7 (4.0–23.1) and G2 vs G3 odds ratios 3.9 (1.7–9.2)). A short data collection period (only one year) and 20% of missing candidates' data are the main limitations of this study. Conclusions: Younger age, English as native language, better results in written part of the exam, working at a European country and the use of PACT for preparation, were factors associated with success in the oral part of the European Diploma in Intensive Care exam. Despite the limitations of this study, the differences in outcome among the exam centres will need further investigation.